Cationic polymer mediated bacterial clustering: cell-adhesive properties of homo- and copolymers - Louzao, Iria; Sui, Cheng; Winzer, Klaus; Fernandez-Trillo, Francisco; Alexander, Cameron (Elsevier, 2015)
New anti-infective materials are needed urgently as alternatives to conventional biocides. It has recently been established that polymer materials designed to bind to the surface of bacteria can induce the formation of cell clusters which enhance the expression of quorum sensing controlled phenotypes. These materials are relevant for anti-infective strategies as they have the potential to inhibit adhesion while at the same time modulating Quorum Sensing (QS) controlled virulence. Here we carefully evaluate the role that charge and catechol moieties in these polymers play on the binding. We investigate the ability of the cationic polymers poly(N-[3-(dimethylamino)propyl] methacrylamide) (pDMAPMAm, P1), poly(N-dopamine methacrylamide-co-N-[3-(dimethylamino)propyl] methacrylamide) (pDMAm-co-pDMAPMAm, P2) and p(3,4-dihydroxy-l-phenylalanine methacrylamide), p(l-DMAm, P3) to cluster a range of bacteria, such as Staphylococcus aureus (Gram-positive), Vibrio harveyi, Escherichia coli and Pseudomonas aeruginosa (Gram-negative) under conditions of varying pH (6, 7 and 8) and polymer concentration (0.1 and 0.5 mg/mL). We identify that clustering ability is strongly dependent on the balance between charge and hydrophobicity. Moreover, our results suggest that catechol moieties have a positive effect on adhesive properties, but only in the presence of cationic residues such as for P2. Overall, our results highlight the subtle interplay between dynamic natural surfaces and synthetic materials, as well as the need to consider synergistic structure–property relationship when designing antimicrobial polymers.